Chrystologiczna oryginalność Testamentu Zabulona (9, 8) - Mielcarek, Krzysztof (The Biblical Annals, 2017)
The article deals with a problematic phrase in TestZab 9, 8 in which mysterious Messiah is portrayed as the holy city – Jerusalem. This obvious Christian interpolation needed some explanation, for neither the person resposible for the final shape of the apocryphon, nor any early Christian writer had commented on it. Up till now this expresssion was usually interpreted as a copist error (Hollander, de Jonge) or simply left with no comment what so ever. The author decided to do a quick research on early Christian literature in order to compare the phrase from TestZab 9, 8 with some christological ideas connected to the holy city in the works of the Church fathers. Few of them: Origen, Hilary of Poitiers and Jerome did write some about Jesus Christ picturing him as New Jerusalem. However, one can hardly prove any impact of TestZab 9, 8 on the thaughts of theses three Church thinkers. It is much more  probable that some biblical traditions and early Church teaching together with some ideas of Philo of Alexandria paved way to their christology in the context of Jerusalem. In this context the phrase about Messiah-Jerusalem is rather an isolated one and thus proves to be either a copist error or a deliberate action of one Christian interpolator which has found no understanding in the later Christian thought.